The Influence of Project-Based Learning and TikTok-Based Digital Media on Learning Outcomes of Fardhu Kifayah Material (Praying for the Dead) - Irwansyah Jul; Afrahul Fadhila Daulai; Sapri Sapri (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to examine the effect of a TikTok-based Project-Based Learning (PjBL) strategy on student learning outcomes in Fardhu Kifayah, specifically the competence of performing funeral prayers at Adhyaksa II Middle School in Medan. This research is a quantitative study with a quasi-experimental approach. The results of the analysis show that the implementation of TikTok-based PjBL strategy has a significant influence on student learning outcomes, as evidenced by a significance value of 0.000 < 0.05 and F count of 13.844 > F table of 3.15. In addition, conventional learning strategies using a whiteboard also show a significant influence, with a significance value of 0.000 and F count of 112.959 > F table of 3.15. This proves that both innovative and traditional strategies can effectively improve learning outcomes, depending on proper implementation. However, the interaction test between the two strategies showed no significant simultaneous effect on learning outcomes (significance 0.566 > 0.05 and Fcount 0.334 < Ftable 3.15). This finding confirms that learning success is more determined by the selection of appropriate and consistent strategies than by an undirected combination of methods.